A look at a small classroom in a big university: through a Metaphor, Vividly - Nikitina, L.; Furuoka, F. (2014)
In educational research literature there are two influential metaphors about learning. They describe this process as either “acquisition” or “participation” (Sfard, 1998). These metaphors have been widely used by scholars, researchers and educators. However, the students’ perspectives on learning have been underexplored. This article addresses this gap in research literature and examines metaphors about learning created by a group of foreign language learners in a big public university in East Malaysia. The findings indicate universality of people’s perceptions about learning and reveal the presence of both the “acquisition” and “participation” metaphors in the students’ images. The study considers the implications of the findings for language pedagogy.